A Comprehensive Review of Risk Assessment Frameworks in Blockchain Applications: Research Gaps and Key Lessons - Rapheal Sunday Amadi; A. S. M. Kayes; Eric Pardede; Mohammad Jabed Morshed Chowdhury; Khandakar Ahmed (IEEE Access, 2025)
Blockchain is a decentralised and distributed digital ledger technology that is used to record and store data securely and transparently and has attracted the attention of both academia and industry. It is imperative to ensure the security of this technology and to understand the potential associated risks. However, in the recent past, blockchain-based applications have suffered from series of security breaches ranging from fraud to smart contract vulnerabilities, wallet theft, private key compromise, and non-regulatory compliance. One of the best ways to identify security threats and the associated risks in blockchain applications is to undertake a proper risk assessment. This paper presents a systematic review of the risk assessment frameworks in blockchain-based applications. We first review the general overview of blockchain technology and examine the up-to-date concepts of blockchain risk management, focusing on risk assessment. Although many scholars have worked on blockchain applications and have published surveys on challenges and opportunities, some on security threats, vulnerabilities, and attacks of blockchain technology, very few have researched blockchain risk management and assessment, and none has proposed a framework for assessing risk in blockchain-based applications. Following our proposed survey methodology, the key contributions of this literature review include a comprehensive assessment of various blockchain applications and their adoption challenges, risks in centralised versus decentralised systems, risk assessment and management in blockchain technologies, and three case studies on the risks of blockchain applications and their real-world implications. Applications discussed include blockchain in healthcare, supply chain management, government, and the Internet of Things (IoT). This review serves as a benchmark for researchers to propose an appropriate risk assessment framework for blockchain applications and to gain a deeper understanding of the associated risks.